Effect of Stimulation to Grow Baby in Bukittinggi City in 2018 - Wiwit Fetrisia; Aisyah Elyanti; Yantri Maputra (Journal of Midwifery, 2018)
The initial stage of a human's life in infancy is considered important because at this time the foundations of personality are laid down which will give color when they grow up. The role of parents is very necessary in providing early stimulation. Stimulation is stimulation that comes from the baby's outer environment. The baby health service coverage in 2014 in Bukittinggi was 88.4%, lower than Padang city as much as 90.6%. It is known that the number of infants aged 0-1 years in Padang city amounted to 3,498 people, while in Bukittinggi city only 629 people. Supposedly with a small number of infants achieving early detection of infant growth and development is better than the number of babies in a larger city. The design of this study was a quasi-experimental design with two group pretest-posttest with the control group to identify the effect of stimulation on infant growth and development before and after the intervention, which was carried out from November 2017 - August 2018, in the environmental health center of Bukittinggi City Health Office. The population is infants with ages 0 - 6 months, and the number of samples taken is 46 people. The results of the study carried out with the Wolcoxon test, obtained there were differences in development before and after the intervention was given to the intervention group p = 0,000, there was a development difference in the control group p = 0.014, there were differences in growth before and after the intervention p = 0.000, there was no difference growth in the control group p = 0.083. It can be concluded that stimulation plays a role in preventing delays in growth and development in infants 0-6 months. From this study health workers can socialize about how to stimulate babies to mothers for early prevention of growth and development disorders in infants.